Exposure of the Portuguese adult population to arsenic: preliminary results of a human biomonitoring study - Namorado, Sónia (2022)
Abstract publicado em: Environ Health Perspect. 2021;1. https://ehp.niehs.nih.gov/doi/abs/10.1289/isee.2021.P-062